Determination of Performance of Different Type of Bailey Bridge of Different Configurations - Thapa, Samir; Suwal, Rajan (Mid-West University Journal of Engineering & Innovation, 2025)
This paper provides a numerical determination of the performance of various type of Bailey bridge configurations, in which the main objective is to determine the maximum response of different configuration. Bailey bridges are modular steel structures made up of interlocking panels connected by pins, allowing them to be quickly assembled and easily adapted to different needs. These modular bridge systems are more susceptible to the effects of dynamic loading due to their flexibility. Four different configurations (Single Truss-Single Storey (SS), Double Truss-Single Storey (DS), Triple Truss-Single Storey (TS), Triple Truss-Double Storey (TD)) for 30m span and Five different configuration (Single Truss- Single Storey (SS), Double Truss-Single Storey (DS), Triple Truss-Single Keywords Storey (TS), Triple Truss-Double Storey (TD), Double Truss- Double Story (DD)) for 60m span were modeled in CSI Bridge and moving load analysis and buckling analysis has been conducted in order to determine the maximum response of bailey bridge members. In order to compare the maximum responses, moving load case is performed for all the structures considering IRC class A vehicle Load. The study shows that TD configuration has higher buckling resistance and increasing number of panels in vertical direction and horizontal direction maximum response mid-span deflection decreases significantly.